An environmental scan of virtual and augmented reality services in academic libraries. Issue 1 (3rd January 2020) - Greene, David; Groenendyk, Michael
Abstract : Purpose: The growing popularity of virtual and augmented reality (VR and AR) technologies, and increased research into their educational uses, has seen them appearing in a significant number of academic libraries. Little is known, however, about how many libraries have actually adopted these technologies or how they have structured library services around them. The purpose of this paper is to answer these questions. Design/methodology/approach: The authors surveyed the websites of the Association of Research Libraries (ARL) member libraries to gather information about the availability of VR and AR equipment as well as information about how access is provided. Recorded details about these services included information about staffing, dedicated space, software, what type of technology was offered and whether or not the technology was lent out or only made available for in-library use. Findings: Results of the research project showed that a significant number of ARL-member libraries do offer access to VR technology. AR technology was much less widespread. The most common technologies offered were the Oculus Rift and HTC Vive. The technology was most typically offered for in-library use only. There were few details about staff or what software was offered to be used with the technology. Originality/value: While there is growing research around how VR and AR is being used in education, little research has been undertaken into how libraries are adopting these technologies. This paper summarizes the research that has been done so far and also takes the next step of providing a larger picture of how widespread the adoption of VR and AR technologies has been within academic libraries, as well as how access to these technologies is being provided.